Exploring Diverse Bioactive Secondary Metabolites from Marine Microorganisms Using Co-Culture Strategy - Li, Xiaolin; Xu, Huayan; Li, Yuyue; Liao, Shengrong; Liu, Yonghong (Molecules (Basel, Switzerland), 2023)
The isolation and identification of an increasing number of secondary metabolites featuring unique skeletons and possessing diverse bioactivities sourced from marine microorganisms have garnered the interest of numerous natural product chemists. There has been a growing emphasis on how to cultivate microorganisms to enhance the chemical diversity of metabolites and avoid the rediscovery of known ones. Given the significance of secondary metabolites as a means of communication among microorganisms, microbial co-culture has been introduced. By mimicking the growth patterns of microbial communities in their natural habitats, the co-culture strategy is anticipated to stimulate biosynthetic gene clusters that remain dormant under traditional laboratory culture conditions, thereby inducing the production of novel secondary metabolites. Different from previous reviews mainly focusing on fermentation conditions or metabolite diversities from marine-derived co-paired strains, this review covers the marine-derived co-culture microorganisms from 2012 to 2022, and turns to a particular discussion highlighting the selection of co-paired strains for marine-derived microorganisms, especially the fermentation methods for their co-cultural apparatus, and the screening approaches for the convenient and rapid detection of novel metabolites, as these are important in the co-culture. Finally, the structural and bioactivity diversities of molecules are also discussed. The challenges and prospects of co-culture are discussed on behave of the views of the authors.